The Spread of Coronavirus Can Be Stopped by Dentists or Not - A Survey - R, DEEPIKA.; ANJALI, A.K. (The journal of contemporary issues in business and government, 2020)
The COVID-19 is a pandemic disease that is transmitted by contamination through the droplets spewed from the infected patient to the common people. Research and Examination on coronavirus are required to provide knowledge on Covid-19 among Dentists and to educate dental practitioners on the importance of spread on COVID -19 transmission. This study raises awareness among the dentist and dental students to prevent the spread of COVID -19 disease to common people. A survey-based self-structured questionnaire was prepared with 15 questions using a random sampling method and was circulated among 100 dental students and dentists through an online portal link. The results were collected and then analysed through SPSS software. Descriptive statistical analysis was carried out and chi square test was used and p value was calculated. The results prove that 53.7% of the dentists want the dental treatments to be carried out, with 94% of the dentists agreeing to use facemask and 94.4 % agreeing to use sanitisers while carrying out procedures. However, 61% of the dentists have expressed their concerns in communicating with the patients soon after the reopening of the clinics.From this study, it was concluded that since the p value was more than 0.05 with respect to anxiety levels in dentists, use of sanitisers for protection,preventive measures taken by dentists and choice of dental treatments carried out, there is no significant statistical difference that has been analysed. Thus the dentist’s role in COVID-19 spread is represented and awareness is created among dentists and dental students and the steps followed by the dentists to prevent the spread of COVID-19 was observed.